BARALEK SEBELUM AKAD NIKAH DI KAMPUNG AKAT NAGARI KAMBANG UTARA KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN (TINJAUAN HISTORIS ANTROPOLOGIS) - Mami Nofrianti; Melia Afdayeni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The implementation of marriage in each region is different from each other. The difference is caused by the cultural pattern of the area concerned. In general, the implementation of marriage is preceded by a marriage contract and inaugurated by means of baralek. Unlike the Lengayang area, one of them in Kampung Akat, the implementation of the marriage contract was preceded by a baralek event. This is a marriage phenomenon that distinguishes it from other regions. The baralek tradition before the marriage contract is carried out by the community because it is already a culture that is received from generation to generation and to maintain the consistency of their customs. This tradition is still maintained by the people today even though the culture of the community has been entered and influenced by outside culture. Regarding the beginning of the emergence of this tradition it is not known for certain but the tradition has existed since the ancestors of the Kampung Akad who descended from Sungai Pagu. The author found several reasons for why the community carried out the barialek before the marriage contract, including to maintain the integrity of Minangkabau women, the influence of outside culture due to the tradition of wandering it had, ijab qabul was the most favored event because it was enlivened with baralek events, and various kinds other assumptions.